Globalization and Health: developing the journal to advance the field. Issue 1 (December 2016) - Martin, Greg; MacLachlan, Malcolm; Labonté, Ronald; Larkan, Fiona; Vallières, Frédérique; Bergin, Niamh
Abstract Founded in 2005, Globalization and Health was the first open access global health journal. The journal has since expanded the field, and its influence, with the number of downloaded papers rising 17-fold, to over 4 million. Its ground-breaking papers, leading authors -including a Nobel Prize winner- and an impact factor of 2.25 place it among the top global health journals in the world. To mark the ten years since the journal's founding, we, members of the current editorial board, undertook a review of the journal's progress over the last decade. Through the application of an inductive thematic analysis, we systematically identified themes of research published in the journal from 2005 to 2014. We identify key areas the journal has promoted and consider these in the context of an existing framework, identify current gaps in global health research and highlight areas we, as a journal, would like to see strengthened.